Rhinoplasty Education Using a Standardized Patient Encounter - Wright, Eric J.; Khosla, Rohit K.; Howell, Lori; Lee, Gordon K. (Archives of Plastic Surgery, 2016)
Background Comprehensive aesthetic surgery training continues to be a challenge for residency programs. Our residency program developed a rhinoplasty-based objective structured clinical examination (OSCE) based upon validated methods as part of the residency education curriculum. We report our experience with the rhinoplasty-based OSCE and offer guidance to its incorporation within residency programs.Methods The encounter involved resident evaluation and operative planning for a standardized patient desiring a rhinoplasty procedure. Validated OSCE methods currently used at our medical school were implemented. Residents were evaluated on appropriate history taking, physical examination, and explanation to the patient of treatment options. Examination results were evaluated using analysis of variance (statistical significance P<0.05).Results Twelve residents completed the rhinoplasty OSCE. Medical knowledge assessment showed increasing performance with clinical year, 50% versus 84% for postgraduate year 3 and 6, respectively (P<0.005). Systems-based practice scores showed that all residents incorrectly submitted forms for billing and operative scheduling. All residents confirmed that the OSCE realistically represents an actual patient encounter. All faculty confirmed the utility of evaluating resident performance during the OSCE as a useful assessment tool for determining the Next Accreditation System Milestone level.Conclusions Aesthetic surgery training for residents will require innovative methods for education. Our examination showed a program-educational weakness in billing/coding, an area that will be improved upon by topic-specific lectures. A thoroughly developed OSCE can provide a realistic educational opportunity to improve residents' performance on the nonoperative aspects of rhinoplasty and should be considered as an adjunct to resident education.
Keywords: Keywords; Rhinoplasty; Educational measurement; Internship and residency